2015
DOI: 10.1007/s15010-015-0793-7
|View full text |Cite
|
Sign up to set email alerts
|

High variability among Emergency Departments in 3rd-generation cephalosporins and fluoroquinolones use for community-acquired pneumonia

Abstract: Cephalosporins and fluoroquinolones use in pneumonia is highly variable among EDs. The majority of these prescriptions are avoidable. Antibiotic stewardship programs should be implemented to restrict their use in EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…Based on institutional guidelines, between 30 and 81% of fluoroquinolone use is inappropriately prescribed within the emergency department and inpatient hospital settings (2,3).…”
mentioning
confidence: 99%
“…Based on institutional guidelines, between 30 and 81% of fluoroquinolone use is inappropriately prescribed within the emergency department and inpatient hospital settings (2,3).…”
mentioning
confidence: 99%
“…The first study population originated from a French academic centre (Centre Hospitalier Universitaire de Nantes, Nantes, France), the study period ranging from January 2002 to December 2015. Patients who were hospitalized between 2002 and 2013 have been described previously [5,20]. The second study population originated from a previously reported multicentre study in seven other French hospitals, including two academic centres [5].…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…Patients who were hospitalized between 2002 and 2013 have been described previously [5,20]. The second study population originated from a previously reported multicentre study in seven other French hospitals, including two academic centres [5]. Local hospital guidance limited the use of 3GCs for community-onset pneumonia in two of the eight hospitals [5].…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…Chez les patients traités aux urgences pour pneumonie, nous avons estimé que 67 % des prescriptions de C3G et/ ou de FQ étaient évitables, c'est-à-dire qu'elles auraient pu être remplacées par un antibiotique à moins large spectre, sélectionnant moins de résistances bactériennes [9]. Par ailleurs, la proportion de traitement par C3G injectable a fortement augmenté entre 2002 et 2012, et il existe une forte variation de la proportion de patients traités par C3G et/ou FQ entre structures d'urgences, indépendamment de la gravité des patients [9,10].…”
Section: Mots Clés Céphalosporines · Fluoroquinolones · Bon Usage Desunclassified
“…Par ailleurs, la proportion de traitement par C3G injectable a fortement augmenté entre 2002 et 2012, et il existe une forte variation de la proportion de patients traités par C3G et/ou FQ entre structures d'urgences, indépendamment de la gravité des patients [9,10]. Ces constats concordants indiquent qu'il existe une surprescription de C3G, et dans une moindre mesure de FQ dans les infections respiratoires basses traitées aux urgences.…”
Section: Mots Clés Céphalosporines · Fluoroquinolones · Bon Usage Desunclassified